The culturable seed mycobiome of two Banksia species is dominated by latent saprotrophic and multi-trophic fungi. Issue 11 (November 2022) - Mertin, A.A.; Laurence, M.H.; van der Merwe, M.; French, K.; Liew, E.C.Y.
Abstract: Seed fungal endophytes play an important beneficial role in the formation of the seedling mycobiome and contribute to plant establishment, but can also occur as latent pathogens and saprotrophs. Current knowledge on the function and diversity of seed fungal endophytes has been gained through studies in agricultural systems whilst knowledge from natural systems is relatively less. We used two co-occurring species from the genus Banksia from four sites in Australia's Sydney Basin Bioregion to investigate the abundance and diversity of seed fungal endophyte communities present in natural ecosystem hosts. Based on results from culturing and DNA sequence analysis of multiple loci, we found that Banksia seeds house a diverse range of fungal endophyte species, that when assigned to functional guilds belonged to multiple trophic modes. Thirty-one of the fungal taxa identified had not been previously reported as endophytes. Amongst the 58 Operational Taxonomic Units identified, Leotiomycetes and Sordariomycetes were the dominant classes and Banksiamyces ( Leotiomycetes ) and Penicillium ( Sordariomycetes ) the dominant genera, with many of the species isolated recorded in the literature as having a limited distribution. The two Banksias shared few fungal endophyte species, which were not always present across all study sites. We revealed a 'hidden diversity' within seeds of Banksia from natural ecosystems and provided insights into the influence host species can have on the seed mycobiome. Highlights: Fifty-eight fungal taxa were isolated from Banksia ericifolia and B. serrata seed. Thirty-one of the 58 seed fungi had not been recorded as seed endophytes previously. Majority of isolated fungi were Banksiamyces and Penicillium. Majority of seed fungi isolated were assigned as saprotrophs or multi-trophic ecologicalmodes. The two Banksia species shared few fungal species, which were not always present across all study sites.